Synthesis, structural refinement and optical behavior of CaTiO3 powders: A comparative study of processing in different furnaces - Cavalcante, L. S.; Marques, V. S.; Sczancoski, J. C.; Escote, M. T.; Joya, M. R.; Varela, José Arana [UNESP]; Santos, M. R. M. C.; Pizani, P. S.; Longo, Elson [UNESP] (Elsevier B.V. Sa, 2008)
Calcium titanate (CaTiO3) powders were synthesized by the polymeric precursor method and processed in different furnaces. The structural evolution of CaTiO3 powders heat treated in conventional furnace and adapted domestic microwave oven was analyzed by X-ray diffraction (XRD), micro-Raman scattering (MRS) spectroscopy and ultraviolet-visible (UV-vis) absorption spectroscopy. XRD, MRS and Rietveld refinement revealed that the CaTiO3 powders heat treated in both furnaces are free of deleterious phases and crystallize in an orthorhombic structure. UV-vis measurements suggested the presence of intermediary energy levels into the optical band gap of structurally disordered CaTiO3 powders. CaTiO3 powders heat treated in microwave oven showed a rapid structural organization than powders heat treated in conventional furnace. The optical absorption values revealed a different behavior due to the changes in the structural order-disorder degree of the CaTiO3 lattice. The differences verified in the heating process of CaTiO3 powders processed in conventional furnace and adapted domestic microwave oven were discussed. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: CaTiO3; optical materials; heat treatment; Rietveld refinement; microwave effects